February revolution 1917 years: instrumental aspect - Andrey Vyacheslavovich Ishin (Проблемы постсоветского пространства, 2017)
One of the most difficult and contradictory periods of domestic history is examined in the article. Thus an author uses the wide circle of the archived materials, allowing completer to expose the specific of state-political process in 1917.